The Influence of Emotional Intelligence, Relationships, Communication, and Social Support on Intimate Partner Violence among Pregnant Women - Yothathip, Hongsavadee; Jittrapirom , Aunchalee; Phanwichakul , Titaree (Journal of The Royal Thai Army Nurses, 2026)
This predictive correlational research aimed to determine the predictive power of emotional intelligence, relationships, communication, and social support on intimate partner violence among pregnant women. The sample consisted of 216 pregnant women, aged 18-44 years, who received antenatal care at a hospital in Surat Thani Province, selected through accidental sampling. The research instruments comprised six questionnaires: 1) demographic characteristics, 2) marital life emotional intelligence, 3) marital relationship quality, 4) marital communication, 5) medical outcomes study: social support survey (MOS-SSS), and 6) abuse assessment scale (AAS). The content validity index (CVI) for these tools was .96, .95, .98, .84, .97, and .89, respectively, with a Cronbach’s alpha coefficient of .78. Data were analyzed by using descriptive statistics and logistic regression. The results revealed that 21.8% of the participants experienced IVP. Emotional intelligence (ß = -.047, p < .05) and marital relationship (ß = -.047, p < .05) had a low-level negative influence, collectively predicting intimate partner violence by 14% (Nagelkerke R² = .14, p < .05). Marital communication and social support were not significant predictors of IPV (p > .05). Recommendations: Emotional intelligence and marital relationship factors should be integrated into violence screening protocols. Furthermore, programs aimed at enhancing emotional intelligence and strengthening marital relationships should be developed to reduce intimate partner violence.